2000
DOI: 10.1002/aic.690460119
|View full text |Cite
|
Sign up to set email alerts
|

Equations of state for the calculation of fluid‐phase equilibria

Abstract: Progress in de®eloping equations of state for the calculation of fluid-phase equilibria is re®iewed. There are many alternati®e equations of state capable of calculating the phase equilibria of a di®erse range of fluids. A wide range of equations of state from cubic equations for simple molecules to theoretically-based equations for molecular chains is considered. An o®er®iew is also gi®en of work on mixing rules that are used to apply equations of state to mixtures. Historically, the de®elopment of equations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
228
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(232 citation statements)
references
References 230 publications
(122 reference statements)
1
228
0
3
Order By: Relevance
“…A recent review on the progress on developing equations of state still consider the expression as perhaps, the most important model for the modification for the van der Waals equation of state. 12 It also emphasizes the accurateness and easiness of its representation of volumetric properties, the requirement of the fewest number of properties (critical pressure and temperature, and acentric factor) for the calculation of the generalized parameters a and b, and the little computer time required for obtain good results as its main advantages. Other works present the Soave's modification 13 to the original equation as a still very useful predictive model for the vapor-liquid equilibrium calculations, mainly for non-polar compounds.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review on the progress on developing equations of state still consider the expression as perhaps, the most important model for the modification for the van der Waals equation of state. 12 It also emphasizes the accurateness and easiness of its representation of volumetric properties, the requirement of the fewest number of properties (critical pressure and temperature, and acentric factor) for the calculation of the generalized parameters a and b, and the little computer time required for obtain good results as its main advantages. Other works present the Soave's modification 13 to the original equation as a still very useful predictive model for the vapor-liquid equilibrium calculations, mainly for non-polar compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The van der Waals (VdW) [29] and Soave-Redlich-Kwong (SRK) [30] are used in this work. Detailed reviews of cubic equations of state can be found in Wei and Sadus [31], for instance.…”
Section: Liquid-to-supercritical-state Transitionmentioning
confidence: 99%
“…Four comprehensive reviews of the development and application of the various types of SAFT have appeared recently [1], [2], [105], [109].…”
Section: Other Modifications Of the Saft Equationmentioning
confidence: 99%
“…A detailed review of the different lines of developing equations of state for the calculation of fluid phase equilibria is given by [1]. Recently [2] presented and discussed in depth both classical and novel thermodynamic models, which have been developed and can potentially be used for industrial applications.…”
Section: Introductionmentioning
confidence: 99%